2015
DOI: 10.5539/jsd.v8n9p226
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Sustainable Forest Management and Community Livelihoods Sustenance in Cameroon: Evidence from the Southern Bakundu Forest Reserve in Southwest Cameroon

Abstract: Sustainable forest management in Cameroon is being plagued with many challenges directly related to key issues in the areas of forest law enforcement and governance. This study used questionnaires to examine the major community livelihood activities undertaken in the SBFR causing deforestation and forest degradation and to explore the localized trigger forces, and their implications for sustainable forest management in Cameroon. The authors found that the rated localized forces triggering indiscriminate human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They concluded that curtailing these setbacks would necessitate the inclusion of these local communities into stakeholder decision making discussions. Also, Ewane et al (2015) reported on the importance of a general national reform policy in forest governance and management such as to ensure future sustainable forest management in Cameroon. The study proposed a participatory approach involving both local forest-dependent communities and government institutions which will foster collaboration and adaptive management in forest management.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that curtailing these setbacks would necessitate the inclusion of these local communities into stakeholder decision making discussions. Also, Ewane et al (2015) reported on the importance of a general national reform policy in forest governance and management such as to ensure future sustainable forest management in Cameroon. The study proposed a participatory approach involving both local forest-dependent communities and government institutions which will foster collaboration and adaptive management in forest management.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, conversion of forest to agricultural land use is not explicitly excluded in the simple management plan of CF in Cameroon and fuel wood collection and illegal timber extraction are highly prevalent [25,21,29,30]. Thus, agricultural and timber exploitation activities are by far the most important economic benefits of local communities at the expense of biodiversity conservation and carbon sequestration in CF [9] and other forest management types in Cameron [14,15,31,32].…”
Section: √ = Positive Government Intervention (Lead To Positive Fores...mentioning
confidence: 99%
“…The higher percentage of forest loss in FR than in PF and PA suggests that FR is less effective in reducing forest loss. Forest reserves as components of PF are technically designated for the production of timber and face significantly greater pressure from illegal timber exploitation and agricultural encroachment of cocoa and food production by adjacent local communities [32].…”
Section: √ = Positive Government Intervention (Lead To Positive Fores...mentioning
confidence: 99%
“…This shows an increasing rate of deforestation for Cameroon in the Congo basin. This increase in deforestation has been linked mainly to timber exports, agriculture, unsustainable and illegal exploitation of timber, infrastructure and fuelwood exploitation (Alemagi & Kozak, 2010;Ewane et al, 2015;Lescuyer et al, 2016;Ngome et al, 2019;Rudel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%